A Review on the Effect of Metal Oxide Nanoparticles on Tribological Properties of Biolubricants - Uniyal, Purva; Gaur, Piyush; Yadav, Jitendra; Khan, Tabrej; Ahmed, Omar Shabbir (ACS omega, 2024)
This review provides a comprehensive and accessible literature review on the integration of nanoparticles into biolubricants to enhance wear and friction regulation, thus improving the overall lubricated system performance. Nanotechnology has significantly impacted various industries, particularly in lubrication. Nanobiolubricants offer promising avenues for enhancing tribological properties. This review focuses on oxide nanoparticles, such as zinc oxide (ZnO), aluminum oxide (Al2O3), copper oxide (CuO), titanium dioxide (TiO2), zirconium dioxide (ZrO2), and graphene oxide (GO) nanoparticles, for their ability to enhance lubricant performance. The impact of nanoparticle concentration on biolubricant properties, including viscosity, viscosity index, flash point temperature, and pour point temperature, is analyzed. The review also addresses potential obstacles and limitations in nanoparticle incorporation, aiming to propose effective strategies for maximizing their benefits. The findings underscore the potential of nanobiolubricants to improve operational efficiency and component lifespan. This review aims to provide valuable insights for researchers, engineers, and professionals in exploring and leveraging nanotechnology’s potential in the lubrication industry. This review paper explores the basics of tribology along with its significance, green principles, mechanisms, and energy savings because of friction, wear, and lubrication. Condition monitoring techniques are also explored to achieve brief knowledge about maintaining reliability and safety of the industrial components. Recent advances in tribology including superconductivity, biotribology, high-temperature tribology, tribological simulation, hybrid polymer composite’s tribology, and cryogenic tribology are investigated, which gives a thorough idea about the subject.